Save the Tabique Construction - Pinto, J.
The main goal of this chapter consists in revising technical building aspects concerning the tabique construction. Tabique is a traditional building technique which applies raw building materials such as timber and earth, for example. External and partition walls are the main tabique building components, which may have a relevant structural performance in the overall stability of a building. In general, the traditional tabique buildings are facing high levels of degradation. This problem is mainly due to the lack of maintenance and technical knowledge. Therefore, reconstruction processes of this type of buildings also require accurate and updated technical information related to materials, to building details, to the main likely pathologies, to the knowledge of the physical and mechanical behaviour of the building components, to the reinforcement solutions, among other aspects. This research work intends to give some guidance in this context and to make a parallel analysis between the Portuguese and the Turkish tabique constructions.